(p+a/v^2)v=RT,derive the cyclic rule.i.e. show the products of the partial derivatives of p,v&T taken in a order is equal to -1?
1 Answer
DISCLAIMER: LONG AND MATH-HEAVY ANSWER!
I am pretty sure that you mean to write
(P + a/(barV^2))barV = RT(P+a¯¯¯V2)¯¯¯V=RT
or
PbarV + a/(barV) = RTP¯¯¯V+a¯¯¯V=RT
THE CYCLIC RULE OF PARTIAL DERIVATIVES
The cyclic rule in general says:
((delx)/(dely))_z((dely)/(delz))_x((delz)/(delx))_y = -1(∂x∂y)z(∂y∂z)x(∂z∂x)y=−1 .
Since
((delbarV)/(delbarT))_P((delT)/(delP))_(barV)((delP)/(delbarV))_(T) = ?(∂¯¯¯V∂¯¯¯T)P(∂T∂P)¯¯¯V(∂P∂¯¯¯V)T=? where
PP is implicitly a function ofTT andbarV¯¯¯V .
PROVING THE CYCLIC RULE USING P, V/n, T
To prove the cyclic rule, write the total derivative of
bb(dP = ((delP)/(delT))_(barV)dT + ((delP)/(delbarV))_TdbarV)
Now if we divide by
cancel(((delP)/(delbarV))_P)^(0) = ((delP)/(delT))_(barV)((delT)/(delbarV))_P + ((delP)/(delbarV))_Tcancel(((delbarV)/(delbarV))_P)^(1)
0 = ((delP)/(delT))_(barV)((delT)/(delbarV))_P + ((delP)/(delbarV))_T
-((delP)/(delbarV))_T = ((delP)/(delT))_(barV)((delT)/(delbarV))_P
Now if you recall that
-((delbarV)/(delT))_P*((delT)/(delP))_(barV)*((delP)/(delbarV))_T = cancel(((delT)/(delP))_(barV)*((delP)/(delT))_(barV)((delbarV)/(delT))_P*((delT)/(delbarV))_P)^(1)
Thus:
color(blue)(((delbarV)/(delT))_P((delT)/(delP))_(barV)((delP)/(delbarV))_T = -1)
APPLYING THE CYCLIC RULE OF PARTIAL DERIVATIVES
To use the cyclic rule for your equation of state, try rewriting it in terms of
P-form of the equation of state
bb(P = (RT)/(barV) - a/(barV^2))
=> color(green)(((delP)/(delbarV))_T = -(RT)/(barV^2) + (2a)/(barV^3))
We can use the reciprocal property of partial derivatives to not have to rewrite this in terms of
=> color(green)(((delT)/(delP))_(barV)) = 1/((delP)/(delT))_(barV)
= 1/(R/(barV)) = color(green)((barV)/R)
T-form of the equation of state
Now to rewrite in terms of
T = 1/R[PbarV + a/(barV)]
=> color(green)(((delbarV)/(delT))_P) = 1/(((delT)/(delbarV))_P)
= 1/[P/R - a/(RbarV^2)]
= 1/[(PbarV^2 - a)/(RbarV^2)]
= color(green)((RbarV^2)/[PbarV^2 - a])
Showing that these derivatives explicitly reduce to -1
Now we combine these to see if we get
((delbarV)/(delT))_P((delT)/(delP))_(barV)((delP)/(delbarV))_T stackrel(?)(=) -1
= (RbarV^2)/[PbarV^2 - a] (barV)/R(-(RT)/(barV^2) + (2a)/(barV^3))
= (RbarV^2)/[PbarV^2 - a] (-(T)/(barV) + (2a)/(RbarV^2))
= -(TRbarV^2)/(barV(PbarV^2 - a)) + (2aRbarV^2)/(RbarV^2(PbarV^2 - a))
= -(TR^2barV^3)/(RbarV^2(PbarV^2 - a)) + (2aRbarV^2)/(RbarV^2(PbarV^2 - a))
Now make sure that you recall that
-x/(a + b) + y/(a + b) = (-(x - y))/(a + b) = -(x - y)/(a + b) .
Thus:
=> (-(TR^2barV^3 - 2aRbarV^2))/(RbarV^2(PbarV^2 - a))
= (-cancel(RbarV^2)(TRbarV - 2a))/(cancel(RbarV^2)(PbarV^2 - a))
= (-(RTbarV - 2a))/(PbarV^2 - a)
Now we substitute
=> (-((PbarV + a/(barV))barV - 2a))/(PbarV^2 - a)
= -(PbarV^2 + a - 2a)/(PbarV^2 - a)
= -cancel((PbarV^2 - a)/(PbarV^2 - a))
=> color(blue)(-1 = ((delbarV)/(delT))_P((delT)/(delP))_(barV)((delP)/(delbarV))_T)
as expected!